Ruthenium on carbon catalyst, method for its preparation and use
Patent Information
- Application Number
- CN202611116394.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-27
AI Technical Summary
[0006]本发明的主要目的在于提供一种钌炭催化剂、其制备方法及应用,以解决现有技术中钌炭催化剂的活性组分分散性差、与载体相互作用薄弱、制备工艺复杂,导致催化选择性与循环稳定性不佳的问题
[0018] During the loading of the active component, a combined technique of "supercritical deposition and in-situ liquid-phase reduction" is employed. The high diffusivity and solubility of supercritical fluids promote the uniform dispersion of ruthenium intermediates on the support surface and within the pores. Subsequent in-situ liquid-phase reduction efficiently converts ruthenium into highly dispersed ruthenium particles, effectively inhibiting Ostwald ripening and agglomeration of ruthenium particles. This significantly increases the number and exposure of catalytic active sites, thereby enhancing catalytic activity. Furthermore, this preparation process is simple, with controllable parameters, requiring no complex equipment, which is conducive to large-scale production. The prepared catalyst exhibits high catalytic activity in the glucose hydrogenation reaction, with significantly improved glucose conversion and sorbitol selectivity. Moreover, its performance remains stable after multiple cycles, enabling the efficient conversion of glucose to sorbitol under mild conditions.
Smart Images

Figure CN122605515B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalytic materials technology, and more specifically, to a ruthenium-carbon catalyst, its preparation method, and its application. Background Technology
[0002] Sorbitol is an important polyol compound widely used in pharmaceuticals, chemicals, light industry, and food. It is also a highly promising energy platform molecule, capable of being further converted into high-value-added products such as fuels, fine chemicals, and hydrogen. Currently, industrially, sorbitol is mainly produced from glucose via catalytic hydrogenation, with traditional processes often using Raney nickel as the core catalyst. However, this type of catalyst suffers from insufficient catalytic activity and poor structural stability, and is prone to particle breakage and pulverization, as well as loss of active components during the reaction. These drawbacks not only limit the further improvement of the purity and quality of sorbitol products but also lead to environmental problems such as byproduct residues and waste pollution.
[0003] Ruthenium-based catalysts have become an ideal alternative to Raney nickel catalysts due to their excellent carbonyl hydrogenation activity, high selectivity, and ability to achieve efficient conversion under mild conditions. Among them, ruthenium-carbon catalysts, as novel catalytic materials for the hydrogenation of glucose to sorbitol, possess advantages such as high activity and good selectivity for the target product. However, existing technologies still have several key challenges:
[0004] First, the ruthenium active component exhibits poor dispersion on the carbon support surface, easily agglomerating into large-sized metal particles, resulting in a significant reduction in effective catalytic active sites. Second, the interfacial interaction between the support and the active component is weak, leading to insufficient binding stability. During repeated catalyst cycles, ruthenium nanoparticles are prone to migration, detachment, and loss, making it difficult to meet industrial requirements in terms of service life. Third, current methods for preparing ruthenium-carbon catalysts commonly employ ruthenium chloride, chlororuthenic acid, sodium chlororuthenate, and other chloride-containing ruthenium salts as active precursors. In aqueous solutions, chloride ions can undergo stepwise coordination with trivalent ruthenium ions, easily forming a structurally stable hexachlororuthenium(III) complex ion [RuCl6] under high chloride concentration conditions. 3- In environments with low chlorine concentrations, a water-chlorine mixed complex ruthenium chloride ion [RuCl] is formed. n (H2O) 6-n ] (3-n)-(n=0~6) These coordinating ions have strong chemical bonds, making it difficult to completely remove bound chloride ions using only conventional water washing processes. Furthermore, during liquid-phase reduction and pyrolysis, residual chloride elements easily remain in the catalyst channels and on the support surface. Residual chloride ions not only poison the noble metal active sites, inhibiting the main hydrogenation reaction and inducing the formation of byproducts such as mannitol, reducing the selectivity of sorbitol, but also exacerbate corrosion of the reaction apparatus, leading to a decrease in the purity of the catalytic product. Fourthly, the traditional ruthenium-carbon catalyst preparation process is cumbersome, involves many steps, and has high raw material and energy consumption, which is unfavorable for large-scale industrial production.
[0005] To address the aforementioned issues, existing technologies have optimized ruthenium-carbon catalysts through methods such as support modification and the introduction of additives. For example, acid treatment is used to functionalize activated carbon supports, introducing oxygen-containing functional groups to enhance the interaction between the support and ruthenium particles; or additives such as boron are introduced to form an amorphous alloy structure, improving catalytic activity and stability. However, the effects of existing support modification are limited, the dispersibility of active components still needs further improvement, and the catalyst's cycle stability remains significantly different from actual industrial requirements. Therefore, developing a highly dispersed, highly selective, long-life, and simple and environmentally friendly ruthenium-carbon catalyst is of great significance for achieving a more efficient and green upgrade of the glucose hydrogenation to sorbitol process. Summary of the Invention
[0006] The main objective of this invention is to provide a ruthenium-carbon catalyst, its preparation method, and its application, in order to solve the problems of poor dispersibility of active components, weak interaction with the support, and complex preparation process in the prior art of ruthenium-carbon catalysts, which lead to poor catalytic selectivity and cycle stability.
[0007] To achieve the above objectives, according to one aspect of the present invention, a method for preparing a ruthenium-carbon catalyst is provided, comprising the following steps: Step S1, oxidizing activated carbon with an acid solution to obtain oxidized activated carbon; activating the oxidized activated carbon with an oxygen-nitrogen mixture to obtain modified activated carbon; Step S2, mixing ruthenium salt with a surfactant and a first solvent to obtain a ruthenium salt solution, introducing CO to carry out a reduction reaction, followed by adding ammonia water to undergo a hydrolysis reaction to obtain a ruthenium(II) hydroxycarbonyl polymer; Step S3, ruthenium(II) hydroxycarbonyl polymer... II) The hydroxycarbonyl polymer is mixed with a complexing agent and a second solvent to obtain an active raw material solution. Modified activated carbon is added for impregnation to obtain an impregnation solution. The impregnation solution is transferred to a reaction vessel and supercritical fluid is introduced for supercritical fluid deposition to obtain a ruthenium-supported pretreated support. In step S4, the ruthenium-supported pretreated support is dispersed in water, a reducing agent is added, and a reduction reaction is carried out to obtain a catalyst precursor. In step S5, the catalyst precursor is sintered in an inert gas atmosphere to obtain a ruthenium-carbon catalyst. The ruthenium-carbon catalyst contains nano-ruthenium particles.
[0008] Furthermore, the ruthenium nanoparticles have a particle size Dv50 of 2-8 nm and a particle size distribution range A = Dv90-Dv10, where A ≤ 5 nm; and / or the ruthenium loading of the ruthenium carbon catalyst is 1.0-5.0 wt% based on 100.0% of the total weight of the ruthenium carbon catalyst; and / or the modified activated carbon has a BET specific surface area of 750-1200 m² / g and a pore volume of 0.8-1.5 cm³ / g; and / or the modified activated carbon surface has oxygen-containing functional groups, including one or more of carboxyl, hydroxyl, and sulfonic acid groups, with an oxygen-containing functional group content of 0.5-2.0 mmol / g.
[0009] Further, in step S1, the activated carbon has a particle size of 20-100 mesh, a BET specific surface area of 700-1100 m² / g, and a pore volume of 0.6-1.2 cm³ / g; and / or the acid solution includes concentrated nitric acid and concentrated sulfuric acid, with a volume ratio of (2-3):1; and / or the oxidation temperature is 80-120℃, and the time is 3-8 h; and / or the volume fraction of O2 in the oxygen-nitrogen mixture is 5.0-10.0%, and the gas flow rate is 150-250 mL / min; and / or the temperature for heating activation is 250-350℃, the time is 1-3 h, and the heating rate is 2-5℃ / min; and / or the step before heating activation includes the following steps: washing the oxidized activated carbon with water until the pH of the washing solution is 5.5-6.5, and then drying it at 105-110℃ for 4-6 h.
[0010] Further, in step S2, the ruthenium salt includes one or more of hydrated ruthenium trichloride, ruthenium chloroacrylic acid, sodium ruthenium chloroacrylate, and potassium ruthenium chloroacrylate; and / or the surfactant includes one or more of stearic acid, Tween, sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, hexadecyltrimethylammonium bromide, and Span; and / or the first solvent includes one or more of water, hydrochloric acid, ethanol, and methanol; and / or the CO gas flow rate is 30~120 mL / min; and / or the molar concentration of the ruthenium salt in the ruthenium salt solution is 0.05~ The surfactant content in the 0.2 mol / L ruthenium salt solution is 0.01–1.0% by weight; the pH of the ruthenium salt solution after the addition of ammonia is 7.5–10.0; the mass concentration of ammonia is 5.0–15.0%; the temperature of the reduction reaction is 55–85 °C, and the time is 4–10 h; the pH of the hydrolysis reaction is 7.5–10.0, the temperature is 30–60 °C, the time is 3–6 h, and the stirring rate is 300–800 rpm.
[0011] Further, in step S3, the complexing agent includes one or more of ethylenediamine, citric acid, oxalic acid, ammonium chloride, and aminotriacetic acid; and / or the second solvent includes one or more of water, ethanol, and methanol; and / or the supercritical fluid includes one or more of supercritical CO2, supercritical N2O, and supercritical NH3; and / or the molar concentration of ruthenium atoms in the ruthenium(II)hydroxycarbonyl polymer in the active raw material solution is 0.01~0.5 mol / L; and / or the molar ratio of the complexing agent to the ruthenium(II)hydroxycarbonyl polymer is (0.01~3):1; and / or the impregnation temperature is 30~60℃, the time is 6~12h, and the stirring is... The stirring rate is 150~300 rpm; and / or the conditions for supercritical fluid deposition include: heating the reactor to 50~150℃, pressurizing it to 5.0~15.0 MPa, holding it at pressure for 1~3 h, and stirring at a rate of 200~400 rpm; after the reaction is completed, cooling the reactor to room temperature at a rate of 1~2℃ / min, and releasing the gas inside the reactor at a depressurization rate of less than 0.5 MPa / min; and / or the supercritical fluid deposition process also includes the following steps: washing the ruthenium-loaded pretreated support alternately with water and anhydrous ethanol 3~5 times, and then vacuum drying it at 80~100℃ for 6~8 h, with a vacuum degree ≤-0.09 MPa.
[0012] Further, in step S4, the reducing agent includes one or more of potassium borohydride, sodium borohydride, hydrazine hydrate, sodium citrate, and ascorbic acid; and / or the molar ratio of the reducing agent to the ruthenium atoms in the ruthenium-loaded pretreated support is (2~5):1; and / or the reducing agent is added in the form of a reducing agent solution; wherein the solvent of the reducing agent solution includes one or more of ethylene glycol, ethanol, and water; and / or the molar concentration of the reducing agent solution is 0.1~0.5 mol / L, the dropping rate is 1~5 mL / min, and stirring is continued for 30~60 min after the dropping is completed; and / or the reduction reaction is carried out under ice-water bath conditions, the temperature of the reduction reaction is 0~5℃, and the time is 1~3 h; and / or the following steps are included after the reduction reaction: the liquid is subjected to solid-liquid separation, the solid product is washed with water until the washing liquid is free of chloride ions, and then vacuum dried at 80~100℃ for 4~6 h, with a vacuum degree ≤-0.09 MPa.
[0013] Further, in step S5, the inert gas includes one or more of nitrogen, argon and helium; and / or the sintering temperature is 300~400℃, the time is 2~4h, the heating rate is 2~5℃ / min, and the inert gas flow rate is 100~200mL / min.
[0014] According to another aspect of the present invention, a ruthenium-carbon catalyst is provided, which is obtained according to the above-described method for preparing the ruthenium-carbon catalyst.
[0015] According to another aspect of the present invention, a method for preparing sorbitol by hydrogenation of glucose is provided, wherein glucose, water and the above-mentioned ruthenium-carbon catalyst are mixed and subjected to catalytic hydrogenation to obtain sorbitol.
[0016] Furthermore, the weight ratio of ruthenium-carbon catalyst to glucose is (0.5~2.0):100; and / or the catalytic hydrogenation temperature is 100~140℃, the hydrogen pressure is 2.0~5.0MPa, and the time is 1~3h.
[0017] The present invention utilizes activated carbon synergistically modified by mixed acid oxidation and gas-phase heating activation as a support, and ruthenium metal as the active component. A stepwise process is employed to prepare a ruthenium-carbon catalyst: support pretreatment modification, preparation of a ruthenium-free intermediate, complexation impregnation, supercritical deposition, liquid-phase reduction, and sintering activation. During support modification, the mixed acid oxidation treatment introduces abundant oxygen-containing functional groups onto the activated carbon surface through oxidative etching. The subsequent gas-phase heating activation process further modulates the support pore structure, constructing a multi-level "micropore-mesopore" pore structure. This enhances the support's anchoring ability to the active component and provides efficient mass transfer channels for reactants and products. The ruthenium-free intermediate is prepared through CO reduction and ammoniation hydrolysis, effectively solving the chloride ion residue problem associated with traditional ruthenium-containing chloride salts and eliminating catalyst poisoning and equipment corrosion at the source.
[0018] During the loading of the active component, a combined technique of "supercritical deposition and in-situ liquid-phase reduction" is employed. The high diffusivity and solubility of supercritical fluids promote the uniform dispersion of ruthenium intermediates on the support surface and within the pores. Subsequent in-situ liquid-phase reduction efficiently converts ruthenium into highly dispersed ruthenium particles, effectively inhibiting Ostwald ripening and agglomeration of ruthenium particles. This significantly increases the number and exposure of catalytic active sites, thereby enhancing catalytic activity. Furthermore, this preparation process is simple, with controllable parameters, requiring no complex equipment, which is conducive to large-scale production. The prepared catalyst exhibits high catalytic activity in the glucose hydrogenation reaction, with significantly improved glucose conversion and sorbitol selectivity. Moreover, its performance remains stable after multiple cycles, enabling the efficient conversion of glucose to sorbitol under mild conditions. Attached Figure Description
[0019] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0020] Figure 1 The diagram shows the specific surface area and pore size distribution of the modified activated carbon carrier in Example 1 and the unmodified activated carbon carrier in Comparative Example 1.
[0021] Figure 2The infrared spectrum of the surface functional groups of the modified activated carbon support in Example 1 is shown below.
[0022] Figure 3 TEM image and size distribution diagram of nano-Ru particles of the ruthenium-carbon catalyst in Example 1;
[0023] Figure 4 The XRD patterns of the ruthenium-carbon catalysts of Example 1 and Comparative Example 1 are shown below.
[0024] Figure 5 The image shows the high-performance liquid chromatography (HPLC) chromatogram for characterizing the catalytic activity of the ruthenium-carbon catalyst in Example 1.
[0025] Figure 6 The graph shows the catalytic conversion rate and selectivity of the ruthenium-carbon catalyst in Example 1. Detailed Implementation
[0026] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.
[0027] As described in the background section of this invention, existing ruthenium-carbon catalysts suffer from poor dispersion of active components, weak interaction with the support, and complex preparation processes, leading to poor catalytic selectivity and cycle stability. To address these issues, in a typical embodiment of this invention, a method for preparing a ruthenium-carbon catalyst is provided, comprising the following steps: Step S1, oxidizing activated carbon with an acid solution to obtain oxidized activated carbon; activating the oxidized activated carbon with an oxygen-nitrogen mixture to obtain modified activated carbon; Step S2, mixing a ruthenium salt with a surfactant and a first solvent to obtain a ruthenium salt solution, introducing CO for reduction, followed by the addition of ammonia water for hydrolysis to obtain a ruthenium(II) hydroxycarbonyl polymer; Step S3, ... Ruthenium(II) hydroxycarbonyl polymer is mixed with a complexing agent and a second solvent to obtain an active raw material solution. Modified activated carbon is added for impregnation to obtain an impregnation solution. The impregnation solution is transferred to a reaction vessel, and supercritical fluid is introduced for supercritical fluid deposition to obtain a ruthenium-supported pretreated support. In step S4, the ruthenium-supported pretreated support is dispersed in water, a reducing agent is added, and a reduction reaction is carried out to obtain a catalyst precursor. In step S5, the catalyst precursor is sintered in an inert gas atmosphere to obtain a ruthenium-carbon catalyst. The ruthenium-carbon catalyst contains nano-ruthenium particles.
[0028] This invention first performs synergistic modification of the carrier, including mixed acid oxidation and gas-phase activation with an oxygen-nitrogen mixture. The activated carbon carrier is optimized through synergistic modification via chemical site construction and physical structure regulation, and modified activated carbon is prepared. The activated carbon is first oxidized with acid, and oxidative etching introduces abundant oxygen-containing functional groups such as carboxyl groups (-COOH), hydroxyl groups (-OH), and sulfonic acid groups (-SO3H), significantly improving the hydrophilicity and chemical active site density of the carrier surface, strengthening its anchoring effect on the ruthenium active component, and solving the problem of weak interaction between the carrier and the active component.
[0029] Further gas-phase activation with an oxygen-nitrogen mixture was performed to optimize the specific surface area and pore size distribution of the support while preserving chemical sites (e.g., by adjusting parameters such as atmosphere ratio, processing temperature, and reaction time) to achieve synergistic modification. The resulting modified activated carbon possesses a high specific surface area, a reasonable pore structure, and abundant oxygen-containing functional groups. It can provide stable deposition sites for the dispersion of active metal ruthenium, improve the anchoring effect of ruthenium precursors and the dispersion stability of active components, and promote efficient contact between raw materials (such as glucose molecules) and active sites and rapid product diffusion during catalysis. In addition, by controlling the surface electronic properties, the dispersion uniformity of activated carbon in supercritical fluids can be improved, which is more conducive to the deposition of active metal salts.
[0030] Subsequently, a chlorine-free ruthenium intermediate was prepared, including CO reduction under normal pressure and ammoniation hydrolysis, to synthesize the ruthenium salt intermediate, namely the ruthenium(II) hydroxycarbonyl polymer (chemical formula [Ru(CO)2(OH)2)). n (The degree of polymerization n is 2~5). This process can efficiently remove chloride ions from ruthenium salt raw materials at the source, solving the problems of catalyst active site poisoning, decreased catalytic selectivity, and shortened service life caused by residual chloride ions in traditional preparation processes.
[0031] Taking ruthenium salts as hydrated ruthenium trichloride as an example, as the initial ruthenium source, it does not exist in the aqueous solution in a simple ionic form, but is mainly distributed in the system as a stable hydrated chloride complex ion. Since chloride ions can form a relatively stable coordination bond with the ruthenium central ion, chloride ions encased inside the coordination layer are difficult to remove by conventional water washing methods. This is the core reason for chloride ion residue and deterioration of catalytic performance in traditional ruthenium salt systems.
[0032] First, using ruthenium salt as a raw material, [Ru(CO)3Cl2]2 is prepared by carbonylation reduction with CO (purity can be 99.9%) at atmospheric pressure. For example, N2 is bubbled through the system for 10 minutes at room temperature to remove dissolved oxygen, and then CO is continuously bubbled. The main reaction equation is: 2RuCl3·3H2O+6CO=[Ru(CO)3Cl2]2+2HCl+6H2O, Ru³ + Selective reduction to Ru² +CO coordinates and replaces the water ligand to generate a chlorinated carbonyl ruthenium dimer. After the reaction is complete, ammonia is added dropwise to the system to adjust the pH value, so as to promote the complete hydrolysis of the chlorinated carbonyl ruthenium dimer complex and convert it into a ruthenium(II) hydroxy carbonyl polymer ([Ru(CO)3Cl2]2+4NH3·H2O→[Ru(CO)2(OH)2]+2NH4Cl+2CO↑+2H2O).
[0033] Under a CO atmosphere, Ru(III) is first selectively reduced to Ru(II) by CO, while CO, acting as a π-acid ligand, gradually replaces the water ligand and coordinates with Ru(II) to generate ruthenium chlorocarbonyl [Ru(CO)3Cl2]2; during this process, Ru³ + →Ru² + The reduction, H2O→CO ligand substitution, and retention of chlorine ligands are carried out in synergy with bridging polymerization; the Ru–Cl bond remains stable under carbonylation conditions; subsequently, ammonolysis of chlorine ligands can occur under ammonia conditions to generate chlorine-free ruthenium(II) hydroxycarbonyl polymer. This ammonolysis dechlorination mechanism can effectively destroy the stable Ru–Cl coordination structure in chlorinated carbonyl ruthenium, making up for the defect that single carbonylation modification cannot remove coordinated chlorine. The obtained chlorine-free hydroxycarbonyl ruthenium polymer intermediate has no coordinated chlorine residue.
[0034] The above process enhances the binding of chloride and ammonium ions, efficiently removes chloride ions, and improves product purity. This high-purity ruthenium(II) hydroxycarbonyl polymer, as an active metal intermediate salt for the catalyst, not only avoids the adverse effects of chloride ions on subsequent catalytic reactions but also promotes the uniform dispersion and efficient loading of active components on the support surface, thereby improving the catalyst's catalytic activity, selectivity, and long-term stability.
[0035] Then, complexation impregnation and supercritical deposition are performed. The ruthenium intermediate, namely the ruthenium(II) hydroxycarbonyl polymer, is combined with a complexing agent in the aqueous phase to form a stable complex system through coordination. The complexing agent generally contains functional groups containing N, O, and other coordinating atoms, which can provide lone pairs of electrons. Ruthenium metal ions combine with empty orbitals to form coordinate bonds, changing the morphology of the ruthenium species in solution (the complexing agent and Ru²⁺). + Coordination forms stable complexes, inhibiting hydrolysis and aggregation, thus creating conditions for subsequent uniform dispersion. Modified activated carbon, with its high specific surface area and abundant oxygen-containing functional groups (carboxyl, hydroxyl, sulfonic acid groups, etc.), achieves stable binding with ruthenium complexes through physical adsorption (van der Waals forces, microporous adsorption) and chemical bonding (coordination bonds, hydrogen bonds). Simultaneously, the steric hindrance effect of the complex ions helps inhibit aggregation, and targeted anchoring of ruthenium species through pre-constructed chemical sites on the support further enhances the uniformity and stability of ruthenium species dispersion.
[0036] To optimize dispersion and carrier wettability, supercritical fluid was introduced into the reactor for deposition. Its high diffusivity accelerates the diffusion of ruthenium species to the carrier surface and micropores. Furthermore, the low viscosity and near-zero surface tension of the supercritical fluid enhance the contact between the active component and the carrier, achieving deep pore penetration. Simultaneously, the high solubility of the supercritical fluid effectively inhibits local agglomeration of ruthenium species, providing a stable mass transfer environment for uniform deposition. Through the synergistic process of complexation, impregnation, and supercritical deposition, a ruthenium-loaded pretreated carrier exhibiting uniform dispersion of ruthenium species, no significant agglomeration, and excellent structural and performance stability can be obtained.
[0037] Finally, liquid-phase reduction and inert sintering were performed to obtain the ruthenium-carbon catalyst. After supercritical fluid deposition, ruthenium species were uniformly dispersed inside and on the surface of the support pores. On this basis, a reducing agent was introduced for in-situ reduction treatment. In this process, on the one hand, the reducing agent can selectively reduce the ruthenium salt (complexed state) on the support surface and in the pores into uniformly sized nanoscale ruthenium particles; on the other hand, the physical confinement effect of the support pore structure can form steric hindrance, effectively hindering the migration, aggregation and agglomeration of nanoscale ruthenium particles. At the same time, the strong interaction between the pre-constructed chemical sites on the support surface and the ruthenium particles (such as chemical bonding and strong adsorption) can further lock the particle positions and maintain their highly dispersed state.
[0038] The catalyst precursor obtained by reduction is sintered under an inert atmosphere, which further enhances the strong metal-support interface interaction between the ruthenium nanoparticles and the modified activated carbon support, forming a dual physicochemical stability mechanism. This effectively inhibits the shedding, migration, and aggregation of ruthenium particles during the reaction, and significantly improves the structural stability and long-term reliability of the catalyst. The resulting ruthenium-carbon catalyst has the structural characteristics of highly dispersed ruthenium nanoparticles and a tight bond between the active component and the support. The catalyst prepared by this invention exhibits excellent comprehensive catalytic performance due to its high dispersion and abundant active sites. Its catalytic performance in hydrogenation reactions is significantly improved, especially for the selective hydrogenation of glucose to sorbitol in the liquid phase, achieving a significant improvement in both glucose conversion and sorbitol selectivity. Furthermore, based on the strong metal-support interface interaction, the catalyst maintains high catalytic activity and selectivity even after multiple cycles.
[0039] In summary, this invention achieves high dispersion and strong interfacial anchoring of ruthenium active components on modified activated carbon supports through a synergistic process involving support modification, preparation of chlorine-free ruthenium intermediates, dispersion deposition, in-situ reduction, and interface-stabilized sintering. This preparation process simplifies the operation and reduces production costs through multi-step synergistic optimization. Simultaneously, this process synergistically enhances catalyst performance: First, through acid oxidation and gas-phase activation synergistic modification, the pore structure of the support is controlled to have a high specific surface area, a suitable mesopore ratio, and a surface chemical environment rich in oxygen-containing functional groups, laying a structural foundation for the loading of active components; Second, through CO carbonyl reduction and ammoniation hydrolysis, a high-purity chlorine-free ruthenium(II) hydroxycarbonyl polymer intermediate is prepared, which, combined with a complexation system and supercritical fluid deep deposition, achieves molecular-level dispersion and uniform loading of ruthenium species throughout the pores; Third, through mild reduction and inert atmosphere interface-stabilized sintering, the migration and aggregation of ruthenium nanoparticles are synergistically suppressed, and the strong interaction between the metal and the support is strengthened, achieving size control and stabilization of nano-ruthenium particles.
[0040] In the selective hydrogenation of glucose to prepare sorbitol, the ruthenium-carbon catalyst prepared by this invention exhibits excellent comprehensive performance, with both glucose conversion and sorbitol selectivity reaching high levels. Moreover, it can maintain stable catalytic efficiency after multiple cycles (8 times or more). It can effectively replace the traditional Raney Ni catalyst, avoiding its defects such as low activity, poor cycle stability, and easy generation of by-products. It provides a new technical route for the green, efficient, and low-cost preparation of sorbitol and has significant industrial application value.
[0041] In a preferred embodiment, the ruthenium nanoparticles have a particle size Dv50 of 2-8 nm and a particle size distribution range A = Dv90-Dv10, where A ≤ 5 nm; and / or the ruthenium loading of the ruthenium-carbon catalyst is 1.0-5.0 wt% based on 100.0% of the total weight of the ruthenium-carbon catalyst. Controlling the particle size of the ruthenium nanoparticles within the above range is preferable, as it promotes high dispersion of the ruthenium active component on the surface of the modified activated carbon support, reduces particle agglomeration to increase active sites, and achieves highly efficient catalytic hydrogenation. The high uniformity of the ruthenium nanoparticle size also contributes to obtaining uniform catalytic activity, thereby improving reaction stability. The ruthenium loading within the aforementioned range can balance the density of active centers and the carrying capacity of the support, providing more sufficient catalytic activity while reducing particle aggregation or pore blockage caused by excessive loading. This achieves strong interaction between ruthenium and the modified activated carbon support while maintaining high specific surface area and pore structure integrity, further improving the conversion efficiency and selectivity of the catalyst in the glucose hydrogenation reaction and enhancing its structural stability during recycling.
[0042] Mixed acid oxidation can introduce a large number of oxygen-containing functional groups on the surface of activated carbon, providing anchoring points for subsequent ruthenium particle loading; gas-phase activation can further optimize the pore structure of activated carbon, increase specific surface area and pore volume, and enhance the thermal stability and structural integrity of the carrier. In a preferred embodiment, the modified activated carbon has a BET specific surface area of 750~1200 m² / g, a pore volume of 0.8~1.5 cm³ / g, and a pore (mesoporous) structure with a pore size of 2~5 nm accounting for ≥60.0%; and / or the modified activated carbon surface has oxygen-containing functional groups, including one or more of carboxyl, hydroxyl and sulfonic acid groups, with an oxygen-containing functional group content of 0.5~2.0 mmol / g.
[0043] When modified activated carbon possesses the aforementioned structural characteristics, it can further enhance the interaction between the support and ruthenium particles, reduce ruthenium particle aggregation, and simultaneously provide excellent diffusion channels for catalytic raw material molecules such as glucose. Introducing oxygen-containing functional groups onto the activated carbon surface through synergistic modification via oxidation and activation is beneficial for enhancing the anchoring and fixation of nano-ruthenium particles by the support, reducing the migration and aggregation of ruthenium components during impregnation and sintering, further optimizing the diffusion behavior of molecules such as glucose within the catalyst channels, and improving the contact efficiency and mass transfer rate between reactants and catalytically active sites. The synergistic effect of these structural characteristics and surface properties can significantly improve the dispersion uniformity and high-temperature thermal stability of nano-ruthenium particles, thereby effectively enhancing the catalytic activity and selectivity of the catalyst in the target catalytic reaction.
[0044] In a preferred embodiment, in step S1, the activated carbon has a particle size of 20-100 mesh, a BET specific surface area of 700-1100 m² / g, and a pore volume of 0.6-1.2 cm³ / g; and / or the acid solution includes concentrated nitric acid and concentrated sulfuric acid in a volume ratio of (2-3):1; and / or the oxidation temperature is 80-120°C for 3-8 h; and / or the O2 volume fraction in the oxygen-nitrogen mixture is 5.0-10.0%, and the gas flow rate is 150-250 mL / min; and / or the temperature for heating activation is 250-350°C for 1-3 h, and the heating rate is 2-5°C / min; and / or the step before heating activation includes the following steps: washing the oxidized activated carbon with water until the pH of the washing solution is 5.5-6.5, and then drying it at 105-110°C for 4-6 h.
[0045] Controlling the activated carbon's physical properties within the aforementioned range allows the support to possess a more suitable pore structure, providing a more uniform and high-specific-surface-area reaction platform for subsequent functional group introduction and active component anchoring. The aforementioned oxidation conditions can more efficiently introduce abundant and stable oxygen-containing functional groups, enhancing the surface polarity and chemical reactivity of the support. Further controlling the activation conditions within the aforementioned range can improve the pore distribution and functional group density on the activated carbon surface, strengthening the interaction and bonding ability between the support and the ruthenium precursor. The synergistic regulation of these physical properties and modification conditions facilitates the formation of a structurally stable, open and interconnected pore system with dense and uniformly distributed surface functional groups in the modified activated carbon. This significantly improves the nucleation density and dispersion uniformity of ruthenium nanoparticles, effectively reducing their migration and aggregation during subsequent sintering, and strengthening the strong metal-support interaction. Ultimately, this achieves high dispersion and firm anchoring of the ruthenium active component, significantly improving the catalyst's activity and stability.
[0046] In a preferred embodiment, in step S2, the ruthenium salt includes one or more of ruthenium trichloride hydrate, ruthenium chloroacrylic acid, sodium ruthenium chloroacrylate, and potassium ruthenium chloroacrylate; and / or the surfactant includes one or more of stearic acid, Tween, sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, hexadecyltrimethylammonium bromide, and Span; and / or the first solvent includes one or more of water, hydrochloric acid, ethanol, and methanol; and / or the CO gas flow rate is 30~120 mL / min; and / or the molar concentration of the ruthenium salt in the ruthenium salt solution is 0. The surfactant content in the ruthenium salt solution is 0.05~0.2 mol / L; and / or the pH of the ruthenium salt solution after adding ammonia is 7.5~10.0; and / or the mass concentration of ammonia is 5.0~15.0%; and / or the temperature of the reduction reaction is 55~85℃, and the time is 4~10h; and / or the pH of the hydrolysis reaction is 7.5~10.0, the temperature is 30~60℃, the time is 3~6h, and the stirring rate is 300~800rpm. Preferably, the first solvent includes water, hydrochloric acid, or a mixture of ethanol and water, and the volume ratio of ethanol to water in the mixed solvent is not limited and can be (0.1~10):1.
[0047] The above-mentioned ruthenium salt was used to prepare chlorocarbonyl ruthenium ([Ru(CO)3Cl2]2) via a CO carbonylation reduction reaction under normal pressure. After the carbonylation reduction reaction was completed, ammonia was slowly added dropwise to the reaction system to adjust the pH value, promoting the controlled hydrolysis and ligand substitution reaction of the chlorocarbonyl ruthenium complex, gradually transforming it into the ruthenium(II) hydroxycarbonyl polymer [Ru(CO)2(OH)2]. nn=2~5. During the reaction, hydroxyl and carbonyl groups in the system can synergistically participate in coordination substitution, efficiently stripping chloride ions from the ruthenium coordination layer. The chloride ions combine with ammonium ions in the system to form ammonium chloride, achieving chloride ion removal and purification of ruthenium intermediates. This effectively solves the problem of residual chloride ions in traditional ruthenium salt preparation processes and eliminates the poisoning effect of chloride ions on the active sites of the catalyst.
[0048] The aforementioned surfactants can inhibit the aggregation of chlorinated carbonyl ruthenium complex particles, increase the reaction specific surface area, and enhance the reaction performance. - Interfacial contact with ammonium ions enables uniform dechlorination. Maintaining the ruthenium concentration within the aforementioned range is preferable, as it improves reaction efficiency while achieving a more suitable particle density, thus facilitating CO diffusion, coordination structure reconstruction, and Cl- concentration. - Dissociation and release provide a good reaction interface, further optimizing the synthesis of ruthenium chloride-free intermediates.
[0049] When the parameters for CO carbonylation reduction and ammonia dechlorination are within the aforementioned range, it is more conducive to the modification and efficient dechlorination of ruthenium salts. By reconstructing the ruthenium coordination configuration through CO reduction in the early stage and regulating the coordination configuration of ruthenium species, the highly stable hydrated ruthenium chloride species is transformed into an easily modified and dechlorinated chlorocarbonyl complex. Then, the coordination chlorine bond is further broken through the ammonia dechlorination reaction to complete the removal of chlorine. This invention, through the synergistic effect of multi-level ligand substitution, breaks the strong Ru-Cl coordination structure in the ruthenium chloride system in stages, fundamentally solving the technical problems of strong coordination stability between chloride ions and ruthenium centers, low dechlorination efficiency of simple water washing, and incomplete dechlorination by single ammonia dechlorination in traditional processes. It effectively solves the problem of chlorine residue and can ultimately prepare a high-purity intermediate ruthenium(II) hydroxycarbonyl polymer.
[0050] The complexing agent can form a stable complex with ruthenium ions, preventing premature precipitation of ruthenium ions during impregnation and promoting uniform dispersion of ruthenium particles. In a preferred embodiment, in step S3, the complexing agent includes one or more of ethylenediamine, citric acid, oxalic acid, ammonium chloride, and aminotriacetic acid; and / or the second solvent includes one or more of water, ethanol, and methanol; and / or the supercritical fluid includes one or more of supercritical CO2, supercritical N2O, and supercritical NH3; and / or the molar concentration of ruthenium atoms in the ruthenium(II)hydroxycarbonyl polymer in the active raw material solution is 0.01~0.5 mol / L; and / or the molar ratio of the complexing agent to the ruthenium(II)hydroxycarbonyl polymer is (0.01~3):1; and / or the impregnation temperature is 30~60℃, the time is 6~12h, and the stirring is carried out. The stirring rate is 150~300 rpm; and / or the conditions for supercritical fluid deposition include: heating the reactor to 50~150℃, maintaining the pressure at 5.0~15.0 MPa for 1~3 hours, and stirring at 200~400 rpm; after the reaction is completed, cooling the reactor to room temperature at a rate of 1~2℃ / min, and releasing the gas inside the reactor at a depressurization rate of less than 0.5 MPa / min; and / or the supercritical fluid deposition process further includes the following steps: washing the ruthenium-loaded pretreated carrier alternately with water and anhydrous ethanol 3~5 times, followed by vacuum drying at 80~100℃ for 6~8 hours, with a vacuum degree ≤-0.09 MPa, to improve the purity of the material. Preferably, the second solvent includes water or a mixture of ethanol and water, and the volume ratio of ethanol to water in the mixed solvent is not limited and can be (0.1~10):1.
[0051] The aforementioned ruthenium salt and complexing agent form a stable and soluble ruthenium-complex system through coordination, effectively inhibiting the hydrolysis and premature precipitation of ruthenium ions in aqueous solution, ensuring the ruthenium precursor exists in a uniform chemical form. Furthermore, the impregnation process allows for more uniform and complete adsorption of the ruthenium precursor on the modified activated carbon surface, effectively preventing the aggregation of chlorine-free ruthenium intermediates. Based on this, utilizing the low viscosity, high diffusion, strong penetration, and extremely low surface tension characteristics of supercritical fluids, and by optimizing process parameters, the ruthenium complex can be efficiently and uniformly transported to the activated carbon surface, achieving uniform deposition of the active component. The synergistic effect of impregnation and supercritical fluid deposition facilitates the control of nano-ruthenium particles during subsequent in-situ reduction and sintering processes, effectively promoting the formation of uniformly sized and fine ruthenium nanoparticles, thereby enhancing the catalytic activity, structural stability, and long-term service life of the ruthenium-carbon catalyst.
[0052] In a preferred embodiment, in step S4, the reducing agent includes one or more of potassium borohydride, sodium borohydride, hydrazine hydrate, sodium citrate, and ascorbic acid; and / or the molar ratio of the reducing agent to the ruthenium atoms in the ruthenium-loaded pretreated carrier is (2~5):1; and / or the reducing agent is added in the form of a reducing agent solution; wherein the solvent of the reducing agent solution includes one or more of ethylene glycol, ethanol, and water; and / or the molar concentration of the reducing agent solution is 0.1~0.5 mol / L, the dropping rate is 1~5 mL / min, and stirring is continued for 30~60 min after the dropping is completed; and / or the reduction reaction is carried out under ice-water bath conditions, the temperature of the reduction reaction is 0~5℃, and the time is 1~3 h; and / or the following steps are included after the reduction reaction: the liquid is subjected to solid-liquid separation, the solid product is washed with water until the washing liquid is free of chloride ions, and then vacuum dried at 80~100℃ for 4~6 h, with a vacuum degree ≤-0.09 MPa.
[0053] Controlling the reduction reaction conditions within the aforementioned range is beneficial for achieving a more moderate degree of ruthenium ion reduction and reducing nanoparticle aggregation. This promotes uniform nucleation and slow growth of ruthenium species on the modified activated carbon surface, resulting in small-sized, well-dispersed nano-ruthenium particles. This significantly increases the number of active sites and atomic utilization, while reducing problems such as uneven ruthenium deposition on the support surface and support structure damage caused by traditional direct addition of solid or high-concentration reducing agents. Ultimately, this significantly enhances the hydrogenation activity and long-term cycle stability of the catalyst. Solid-liquid separation of the feed solution is performed using methods such as vacuum filtration. The solid product is washed with water until the washing liquid is free of chloride ions, further removing residual impurities and unreacted reducing agents, thus improving material purity.
[0054] In a preferred embodiment, in step S5, the inert gas includes one or more of nitrogen, argon, and helium; and / or the sintering temperature is 300~400℃, the time is 2~4h, the heating rate is 2~5℃ / min, and the inert gas flow rate is 100~200mL / min. Low-temperature activation can further enhance the interaction between ruthenium particles and the support, stabilize the amorphous structure, promote the uniform nucleation of nano-ruthenium particles on the surface of the modified activated carbon support, and achieve strong chemical bonding with oxygen-containing functional groups, significantly reducing the migration and aggregation behavior of ruthenium particles at high temperatures, thereby greatly improving the thermodynamic stability of ruthenium nanoparticles and the bonding strength with the support, and improving the activity and structural integrity of the catalyst during long-term cyclic use.
[0055] In another typical embodiment of the present invention, a ruthenium-carbon catalyst is also provided, which is prepared according to the above-described method. It has significantly improved dispersion of active components, strong interaction between ruthenium and support, and a simple preparation process. It exhibits high conversion rate and high selectivity for sorbitol in glucose hydrogenation reaction and maintains stable performance after multiple cycles. It is suitable for continuous production of sorbitol under mild conditions and has good prospects for industrial application.
[0056] In another typical embodiment of the present invention, a method for preparing sorbitol by hydrogenation of glucose is also provided. Glucose, water, and the aforementioned ruthenium-carbon catalyst are mixed and subjected to catalytic hydrogenation to obtain sorbitol. The above method, employing the ruthenium-carbon catalyst of this application, can achieve highly efficient and selective conversion of glucose under mild reaction conditions. The high-density oxygen-containing functional groups and hierarchical porous structure in the catalyst synergistically promote the adsorption and diffusion of glucose molecules. The nanoscale ruthenium active centers ensure that the hydrogenation reaction pathway is highly selectively directed towards sorbitol, inhibiting the formation of byproducts such as mannitol. Simultaneously, the catalyst possesses excellent structural stability due to the strong interaction between it and the support. After multiple cycles, its activity and selectivity decline significantly lower than that of traditional nickel-based systems, making it suitable for continuous industrial production. This effectively reduces energy consumption and post-processing costs, and improves product purity and process economy.
[0057] In a preferred embodiment, the weight ratio of ruthenium-carbon catalyst to glucose is (0.5~2.0):100; and / or the catalytic hydrogenation temperature is 100~140℃, the hydrogen pressure is 2.0~5.0 MPa, and the time is 1~3 h. Preferably, glucose is mixed with water to obtain a glucose aqueous solution, and then the glucose aqueous solution is mixed with the ruthenium-carbon catalyst, the mass concentration of the glucose aqueous solution being 20~60%. Preferably, the catalytic hydrogenation is carried out under stirring at a stirring rate of 1000~1500 rpm, preferably 1200~1300 rpm. The above conditions are beneficial for achieving efficient utilization of the catalyst active sites. At the same time, this temperature and pressure range can significantly improve the dissolution and diffusion efficiency of hydrogen in the liquid phase, allowing the hydrogenation reaction to proceed stably under mild conditions, significantly inhibiting the formation of byproducts such as dehydration and isomerization, and allowing the dispersion advantage of the ruthenium active component on the support to be more fully utilized, thereby synergistically achieving high glucose conversion and high selectivity of sorbitol.
[0058] Typical, but not limiting, ruthenium nanoparticles have a particle size Dv50 of 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, or any two of these values.
[0059] Typical, but not limiting, the ruthenium loading of the ruthenium-carbon catalyst, based on 100.0% of the total weight of the ruthenium-carbon catalyst, is 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt%, 3.0 wt%, 3.5 wt%, 4.0 wt%, 4.5 wt%, 5.0 wt%, or any two of these values.
[0060] Typically, but not limitingly, in step S1, the volume fraction of O2 in the oxygen-nitrogen mixture is 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, or any two of these values; the gas flow rate is 150 mL / min, 180 mL / min, 200 mL / min, 220 mL / min, 250 mL / min, or any two of these values; and the activation temperature is 250℃, 260℃, 280℃, 300℃, 320℃, 340℃, 350℃, or any two of these values.
[0061] Typically, but not limitingly, in step S2, the molar concentration of the ruthenium salt in the ruthenium salt solution is within the range of 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.18 mol / L, 0.2 mol / L, or any two of these values; the CO gas flow rate is within the range of 30 mL / min, 60 mL / min, 80 mL / min, 100 mL / min, 120 mL / min, or any two of these values; and the surfactant weight percentage... The ammonia content is 0.01%, 0.03%, 0.05%, 0.07%, 0.09%, 0.1%, 0.2%, 0.5%, 0.6%, 0.8%, 1.0%, or any two of these values; the pH value after adding ammonia is 7.5, 8.0, 8.5, 9.0, 9.2, 9.4, 9.5, 9.6, 9.8, 10.0, or any two of these values; the ammonia concentration is 5.0%, 8.0%, 10.0%, 12.0%, 15.0%, or any two of these values.
[0062] Typically, but not limitingly, in step S2, the reduction reaction temperature is 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, or any two of these values, and the time is 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any two of these values; the hydrolysis reaction temperature is 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, or any two of these values, and the time is 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, or any two of these values.
[0063] Typically, but not limitingly, in step S3, the molar concentration of ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer in the active raw material solution is 0.01 mol / L, 0.03 mol / L, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, or 0.5 mol / L; the molar ratio of the complexing agent to the ruthenium(II) hydroxycarbonyl polymer is 0.01:1, 0.02:1, 0.025:1, 0.03:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, or any two of these values within a range.
[0064] Typically, but not limitingly, in step S4, the molar ratio of the reducing agent to ruthenium atoms in the ruthenium-loaded pretreated support is 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, or any two of these values.
[0065] Typically, but not limitingly, in step S5, the sintering temperature is 300°C, 320°C, 340°C, 350°C, 360°C, 380°C, 400°C, or a range of any two of these values.
[0066] In a typical but not limiting method for the hydrogenation of glucose to prepare sorbitol, the weight ratio of ruthenium-carbon catalyst to glucose is 0.5:100, 0.8:100, 1.0:100, 1.2:100, 1.5:100, 1.8:100, 2.0:100, or any two of these values.
[0067] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.
[0068] Example 1
[0069] 1. Preparation of Ruthenium-Carbon Catalyst
[0070] Step S1, carrier pretreatment modification: (1) Mixed acid oxidation: Take 10.0g of activated carbon (particle size of 20~60 mesh, BET specific surface area of 739m² / g, pore volume of 0.75cm³ / g), place it in 50mL of a mixture of concentrated nitric acid and concentrated sulfuric acid with a volume ratio of 2:1, reflux at 100℃ for 5h, filter and wash with deionized water until the pH of the washing solution is 6.0, dry at 110℃ for 5h to obtain purified oxidized activated carbon; (2) Gas phase activation: Place the purified oxidized activated carbon in a tube furnace, introduce a mixture of oxygen and nitrogen with an O2 volume fraction of 8.0%, gas flow rate of 200mL / min, heat to 300℃ at a rate of 3℃ / min, activate for 2h, and cool naturally to room temperature to obtain modified activated carbon.
[0071] Step S2, CO reduction-ammoniation hydrolysis dechlorination: Weigh ruthenic acid, add surfactant (polyvinylpyrrolidone), dissolve in 40 mL of deionized water to prepare a ruthenic salt mixture, wherein the ruthenic salt molar concentration is 0.1 mol / L and the surfactant content is 0.05%. Introduce 99.9% pure CO at a flow rate of 90 mL / min, reduce at 60 °C for 5 h, then add 15.0% ammonia to adjust the pH of the system to 10.0, and hydrolyze at 55 °C and 500 rpm for 4 h to obtain ruthenic(II) hydroxycarbonyl polymer.
[0072] Step S3, Complexation Impregnation-Supercritical Fluid Deposition: A complexing agent (citric acid) is added to the ruthenium(II) hydroxycarbonyl polymer solution, and deionized water is added to a total volume of 50 mL to obtain an active raw material solution. The molar concentration of ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer is 0.05 mol / L, and the molar ratio of the complexing agent to the ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer is 1:1. 5.0 g of the modified activated carbon is added, and the mixture is stirred and impregnated at 45°C and 200 rpm for 8 h to obtain an impregnation solution. The impregnation solution is transferred to a high-pressure reactor, supercritical CO2 is introduced, the temperature is raised to 80°C, the pressure is controlled at 10.0 MPa, and the pressure is maintained for 2 h. During the deposition process, the stirring rate is 300 rpm. After the reaction is completed, the reactor is cooled to room temperature at a rate of 1.5°C / min, and the gas inside the reactor is slowly released at a depressurization rate of 0.3 MPa / min. The product was washed four times alternately with water and anhydrous ethanol, and then dried under vacuum at 90°C for 7 hours at a vacuum degree of -0.095 MPa to obtain the purified ruthenium-loaded pretreated carrier.
[0073] Step S4, Liquid-phase reduction: The purified ruthenium-supported pretreated support was redispersed in 50 mL of deionized water and placed in an ice-water bath (reduction temperature 0-3℃). A 0.3 mol / L reducing agent (sodium borohydride) aqueous solution was slowly added dropwise at a rate of 3 mL / min. The molar ratio of the reducing agent to ruthenium atoms in the ruthenium-supported pretreated support was 3:1. After the addition was complete, the mixture was stirred for 45 min and kept at this temperature for 2 h. After the reaction was completed, the mixture was separated by filtration, washed three times with deionized water, and dried under vacuum at 85℃ for 5 h at a vacuum degree of -0.095 MPa to obtain the purified catalyst precursor.
[0074] Step S5, sintering activation: The purified catalyst precursor is placed in a tube furnace, a nitrogen atmosphere is introduced, the gas flow rate is 150 mL / min, the temperature is increased to 350℃ at 3℃ / min, sintering is carried out for 3 hours, and then naturally cooled to room temperature to obtain the ruthenium-carbon catalyst.
[0075] 2. Selective hydrogenation of glucose to prepare sorbitol
[0076] Take 50 mL of glucose aqueous solution with a mass concentration of 0.5 g / mL, add 0.5 g of the prepared ruthenium-carbon catalyst (the weight ratio of ruthenium-carbon catalyst to glucose is 2:100), place it in a high-pressure reactor, replace the air in the reactor with hydrogen gas 4 times, then introduce hydrogen gas to 3.0 MPa, raise the temperature to 120℃, stir at 1200 rpm, and react for 1.5 h.
[0077] Example 2
[0078] 1. Preparation of Ruthenium-Carbon Catalyst
[0079] Step S1, carrier pretreatment modification: (1) Mixed acid oxidation: Take 10.0g of activated carbon (particle size of 20~60 mesh, BET specific surface area of 724m² / g, pore volume of 0.61cm³ / g), place it in 60mL of a mixture of concentrated nitric acid and concentrated sulfuric acid with a volume ratio of 3:1, reflux at 110℃ for 4h, filter and wash with deionized water until the pH of the washing solution is 6.2, dry at 100℃ for 4.5h to obtain purified oxidized activated carbon; (2) Gas phase activation: Place the purified oxidized activated carbon in a tube furnace, introduce a mixture of oxygen and nitrogen with a volume fraction of 10.0% O2, gas flow rate of 220mL / min, heat to 300℃ at a rate of 4℃ / min, activate for 1.5h, and cool naturally to room temperature to obtain modified activated carbon.
[0080] Step S2, CO reduction-ammoniation hydrolysis dechlorination: Weigh hydrated ruthenium trichloride, add surfactant (hexadecyltrimethylammonium bromide), dissolve in 50 mL of a mixed solvent of ethanol and water to prepare a ruthenium salt mixture, wherein the molar concentration of ruthenium salt is 0.17 mol / L and the content of surfactant is 0.06%. Introduce 99.9% pure CO at a flow rate of 100 mL / min, reduce at 55 °C for 4 h, then add 10.0% ammonia to adjust the pH of the system to 10.0, and hydrolyze at 58 °C and 600 rpm for 5 h to obtain ruthenium(II) hydroxycarbonyl polymer.
[0081] Step S3, Complexation Impregnation-Supercritical Fluid Deposition: A complexing agent (ethylenediamine) is added to the ruthenium(II) hydroxycarbonyl polymer solution, and ethanol is added to bring the total volume to 60 mL to obtain an active raw material solution. The molar concentration of ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer is 0.5 mol / L, and the molar ratio of the complexing agent to the ruthenium atoms in the ruthenium hydroxycarbonyl polymer is 0.4:1. 5.0 g of the modified activated carbon is added, and the mixture is stirred and impregnated at 50 °C and 250 rpm for 6 h to obtain an impregnation solution. The impregnation solution is transferred to a high-pressure reactor, supercritical CO2 is introduced, the temperature is raised to 100 °C, the pressure is controlled at 12.0 MPa, and the pressure is maintained for 1.5 h. During the deposition process, the stirring rate is 350 rpm. After the reaction is complete, the reactor is cooled to room temperature at a rate of 1.2 °C / min, and the gas inside the reactor is slowly released at a depressurization rate of 0.4 MPa / min. The product was washed five times alternately with water and anhydrous ethanol, and then dried under vacuum at 95°C for 6.5 h at a vacuum degree of -0.098 MPa to obtain the purified ruthenium-loaded pretreated carrier.
[0082] Step S4, Liquid-phase reduction: The purified ruthenium-supported pretreated support was redispersed in 60 mL of deionized water and placed in an ice-water bath (reduction temperature 0-3℃). A 0.4 mol / L reducing agent (potassium borohydride) aqueous solution was slowly added dropwise at a rate of 2 mL / min. The molar ratio of the reducing agent to ruthenium atoms in the ruthenium-supported pretreated support was 4:1. After the addition was complete, the mixture was stirred for 30 min and kept at this temperature for 1.5 h. After the reaction was completed, the mixture was filtered and separated, washed three times with deionized water, and dried under vacuum at 90℃ for 4.5 h at a vacuum degree of -0.098 MPa to obtain the purified catalyst precursor.
[0083] Step S5, sintering activation: The purified catalyst precursor is placed in a tube furnace, an argon atmosphere is introduced, the gas flow rate is 180 mL / min, the temperature is increased to 380℃ at 4℃ / min, sintering is carried out for 2.5 h, and then naturally cooled to room temperature to obtain the ruthenium-carbon catalyst.
[0084] 2. Selective hydrogenation of glucose to prepare sorbitol
[0085] Take 50 mL of glucose aqueous solution with a mass concentration of 0.4 g / mL, add 0.4 g of the prepared ruthenium-carbon catalyst (the weight ratio of ruthenium-carbon catalyst to glucose is 2:100), place it in a high-pressure reactor, replace the air in the reactor with hydrogen gas 4 times, then introduce hydrogen gas to 4.0 MPa, raise the temperature to 130℃, stir at 1300 rpm, and react for 1 h.
[0086] Example 3
[0087] The difference from Example 1 is that in the preparation of the ruthenium-carbon catalyst, in step S1, the support pretreatment modification is as follows: (1) Mixed acid oxidation: Take 10.0g of activated carbon (particle size of 20~60 mesh, BET specific surface area of 704m² / g, pore volume of 1.2cm³ / g), place it in 50mL of a mixture of concentrated nitric acid and concentrated sulfuric acid with a volume ratio of 2:1, reflux at 80℃ for 8h, filter and wash with deionized water until the pH of the washing solution is 5.5, dry at 105℃ for 6h to obtain purified oxidized activated carbon; (2) Gas phase activation: Place the purified oxidized activated carbon in a tube furnace, introduce a mixture of oxygen and nitrogen with a volume fraction of 5.0% O2, gas flow rate of 250mL / min, heat to 250℃ at a rate of 2℃ / min, activate for 3h, and cool naturally to room temperature to obtain modified activated carbon.
[0088] Example 4
[0089] The difference from Example 1 is that in the preparation of the ruthenium-carbon catalyst, in step S1, the support pretreatment modification is as follows: (1) Mixed acid oxidation: Take 10.0g of activated carbon (particle size of 20~60 mesh, BET specific surface area of 1082m² / g, pore volume of 0.86cm³ / g), place it in 50mL of a mixture of concentrated nitric acid and concentrated sulfuric acid with a volume ratio of 3:1, reflux at 120℃ for 3h, filter and wash with deionized water until the pH of the washing solution is 6.5, dry at 110℃ for 4h to obtain purified oxidized activated carbon; (2) Gas phase activation: Place the purified oxidized activated carbon in a tube furnace, introduce a mixture of oxygen and nitrogen with a volume fraction of 10.0% O2, gas flow rate of 150mL / min, heat to 350℃ at a rate of 5℃ / min, activate for 1h, and cool naturally to room temperature to obtain modified activated carbon.
[0090] Example 5
[0091] The difference from Example 1 is that in the preparation of the ruthenium-carbon catalyst, in step S2, CO reduction-ammoniation hydrolysis dechlorination: ruthenium trichloride hydrate is weighed, a surfactant (polyvinylpyrrolidone) is added, and dissolved in 40 mL of deionized water to prepare a ruthenium salt mixture, wherein the molar concentration of ruthenium salt is 0.05 mol / L and the content of surfactant is 0.1%. 99.9% pure CO is introduced at a flow rate of 50 mL / min, and reduction is carried out at 65 °C for 6 h. Subsequently, 8.0% ammonia is added to adjust the pH of the system to 9.0, and hydrolysis is carried out at 50 °C and 300 rpm for 6 h to obtain ruthenium(II) hydroxycarbonyl polymer.
[0092] Example 6
[0093] The difference from Example 1 is that in the preparation of the ruthenium-carbon catalyst, in step S2, CO reduction-ammoniation hydrolysis dechlorination: Sodium ruthenium chloride is weighed, and a surfactant (sodium dodecylbenzenesulfonate) is added and dissolved in 40 mL of deionized water to prepare a ruthenium salt mixture, wherein the molar concentration of ruthenium salt is 0.2 mol / L and the content of surfactant is 1.0%. 99.9% pure CO is introduced at a flow rate of 30 mL / min, and reduction is carried out at 85 °C for 9 h. Subsequently, 10.0% ammonia water is added to adjust the pH of the system to 8.5, and hydrolysis is carried out at 60 °C and 800 rpm for 3 h to obtain ruthenium(II) hydroxycarbonyl polymer.
[0094] Example 7
[0095] The difference from Example 1 lies in the preparation of the ruthenium-carbon catalyst. In step S3, the complexation impregnation-supercritical fluid deposition involves adding a complexing agent (ethylenediamine) to a ruthenium(II) hydroxycarbonyl polymer solution and replenishing it with deionized water to obtain an active raw material solution. The molar concentration of ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer is 0.05 mol / L, and the molar ratio of the complexing agent to the ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer is 1:1. 5.0 g of the modified activated carbon is added, and the mixture is stirred and impregnated at 30°C and 150 rpm for 12 h to obtain an impregnation solution. The impregnation solution is transferred to a high-pressure reactor, supercritical N2O is introduced, the temperature is raised to 50°C, the pressure is controlled at 15.0 MPa, and the pressure is maintained for 3 h. During the deposition process, the stirring rate is 400 rpm. After the reaction is complete, the reactor is cooled to room temperature at a rate of 1°C / min, and the gas inside the reactor is slowly released at a depressurization rate of 0.1 MPa / min. The product was washed three times alternately with water and anhydrous ethanol, and then dried under vacuum at 80°C for 8 hours at a vacuum degree of -0.09 MPa to obtain the purified ruthenium-loaded pretreated carrier.
[0096] Example 8
[0097] The difference from Example 1 lies in the preparation of the ruthenium-carbon catalyst. In step S3, the complexation impregnation-supercritical fluid deposition involves adding a complexing agent (oxalic acid) to a ruthenium(II) hydroxycarbonyl polymer solution and replenishing it with deionized water to obtain an active raw material solution. The molar concentration of ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer is 0.5 mol / L, and the molar ratio of the complexing agent to the ruthenium atoms in the ruthenium hydroxycarbonyl polymer is 3:1. 5.0 g of the modified activated carbon is added, and the mixture is stirred and impregnated at 60°C and 300 rpm for 6 hours to obtain an impregnation solution. The impregnation solution is transferred to a high-pressure reactor, supercritical NH3 is introduced, the temperature is raised to 150°C, the pressure is controlled at 5.0 MPa, and the pressure is maintained for 1 hour. During the deposition process, the stirring rate is 200 rpm. After the reaction is complete, the reactor is cooled to room temperature at a rate of 2°C / min, and the gas inside the reactor is slowly released at a depressurization rate of 0.5 MPa / min. The product was washed five times alternately with water and anhydrous ethanol, and then dried under vacuum at 100°C for 6 hours at a vacuum degree of -0.09 MPa to obtain the purified ruthenium-loaded pretreated carrier.
[0098] Example 9
[0099] The difference from Example 1 lies in the preparation of the ruthenium-carbon catalyst. In step S4, during liquid-phase reduction, the purified ruthenium-supported pretreated support is redispersed in deionized water and placed in an ice-water bath (reduction temperature 0-3℃). A 0.5 mol / L reducing agent (hydrazine hydrate) aqueous solution is slowly added dropwise at a rate of 1 mL / min, with a molar ratio of reducing agent to ruthenium atoms in the ruthenium-supported pretreated support of 2:1. After the addition is complete, stirring is continued for 30 min, and the reduction is maintained at this temperature for 3 h. After the reaction is complete, the mixture is separated by filtration, washed three times with deionized water, and dried under vacuum at 80℃ for 6 h at a vacuum degree of -0.09 MPa to obtain the purified catalyst precursor.
[0100] Example 10
[0101] The difference from Example 1 lies in the preparation of the ruthenium-carbon catalyst. In step S4, during liquid-phase reduction, the purified ruthenium-supported pretreated support is redispersed in deionized water and placed in an ice-water bath (reduction temperature 0-3℃). A 0.1 mol / L reducing agent (sodium citrate) aqueous solution is slowly added dropwise at a rate of 5 mL / min, with a molar ratio of reducing agent to ruthenium atoms in the ruthenium-supported pretreated support of 5:1. After the addition is complete, stirring continues for 60 min, and the reduction is maintained at this temperature for 1 h. After the reaction is complete, the mixture is separated by filtration, washed three times with deionized water, and dried under vacuum at 100℃ for 4 h at a vacuum degree of -0.09 MPa to obtain the purified catalyst precursor.
[0102] Example 11
[0103] The difference from Example 1 is that in the preparation of the ruthenium-carbon catalyst, in step S5, sintering activation: the purified catalyst precursor is placed in a tube furnace, a nitrogen atmosphere is introduced, the gas flow rate is 100 mL / min, the temperature is increased to 300°C at 2°C / min, sintering is carried out for 4 hours, and then naturally cooled to room temperature to obtain the ruthenium-carbon catalyst.
[0104] The selective hydrogenation of glucose to prepare sorbitol involves: taking 50 mL of a glucose aqueous solution with a mass concentration of 0.4 g / mL, adding the prepared ruthenium-carbon catalyst (the weight ratio of ruthenium-carbon catalyst to glucose is 0.5:100), placing it in a high-pressure reactor, purging the reactor with hydrogen gas to replace the air in the reactor 4 times, then purging with hydrogen gas to 2.0 MPa, raising the temperature to 140 °C, stirring at a speed of 1200 rpm, and reacting for 1 h.
[0105] Example 12
[0106] The difference from Example 1 is that in the preparation of the ruthenium-carbon catalyst, in step S5, sintering activation: the purified catalyst precursor is placed in a tube furnace, a nitrogen atmosphere is introduced, the gas flow rate is 200 mL / min, the temperature is increased to 400°C at 5°C / min, sintering is carried out for 2 hours, and then naturally cooled to room temperature to obtain the ruthenium-carbon catalyst.
[0107] The selective hydrogenation of glucose to prepare sorbitol involves: taking 50 mL of a glucose aqueous solution with a mass concentration of 0.4 g / mL, adding the prepared ruthenium-carbon catalyst (the weight ratio of ruthenium-carbon catalyst to glucose is 2.0:100), placing it in a high-pressure reactor, purging the reactor with hydrogen gas to replace the air in the reactor 4 times, then purging with hydrogen gas to 5.0 MPa, heating to 100 °C, stirring at 1200 rpm, and reacting for 3 h.
[0108] Comparative Example 1
[0109] The difference from Example 1 is that step S1 was not performed in the preparation of the ruthenium-carbon catalyst.
[0110] Comparative Example 2
[0111] The difference from Example 1 is that no complexing agent was added in step S3 during the preparation of the ruthenium-carbon catalyst.
[0112] Comparative Example 3
[0113] The difference from Example 1 is that step S5 was not performed in the preparation of the ruthenium-carbon catalyst.
[0114] Comparative Example 4
[0115] The difference from Example 1 is that step S2 was not performed in the preparation of the ruthenium-carbon catalyst, and an equimolar amount of ammonium chlororuthenate aqueous solution was used instead of the ruthenium(II) hydroxycarbonyl polymer solution.
[0116] Comparative Example 5
[0117] The difference from Example 1 is that in the preparation of the ruthenium-carbon catalyst, supercritical fluid deposition was not performed in step S3.
[0118] Comparative Example 6
[0119] The difference from Example 1 is that in the preparation of the ruthenium-carbon catalyst, in step S3, the solvent is completely removed by drying at 60°C and vacuum degree ≤ -0.09MPa for 24h to obtain a dried ruthenium-containing pretreated support (replacing supercritical fluid deposition); then the dried ruthenium-containing pretreated support is placed in a tube furnace, and a mixed gas containing 10% hydrogen and the remainder nitrogen is introduced at a gas flow rate of 200mL / min. The temperature is increased to 350°C at 5°C / min and held for 4h for in-situ thermal reduction. After natural cooling to room temperature, the ruthenium-carbon catalyst is obtained.
[0120] Performance testing:
[0121] The above embodiments and comparative examples were subjected to the following tests, and the results are shown in Tables 1 and 2.
[0122] BET specific surface area of modified activated carbon: The N2 adsorption-desorption isotherm of modified activated carbon was measured at 77 K using the liquid nitrogen adsorption-desorption method (BET method), and the specific surface area was calculated using the Brunauer-Emmett-Teller (BET) model.
[0123] Pore volume and pore size distribution of modified activated carbon: Based on the N2 adsorption-desorption isotherms obtained from BET tests, the pore volume and pore size distribution of mesopores (2~50nm) were calculated using the Barrett-Joyner-Halenda (BJH) model, and the pore volume of micropores (<2nm) was calculated using the t-plot method. The total pore volume is the sum of the pore volumes of micropores and mesopores.
[0124] Total surface functional group content of modified activated carbon: The total surface functional group content was determined by Boehm titration. The functional groups of the modified activated carbon were characterized using a Nicolet 6700 Fourier transform infrared spectrometer (FTIR) from NICOLET (USA). Test conditions: spectral range 400–4000 cm⁻¹ -1 32 scans, 4cm resolution -1 A blank sample was collected as background before the test, and the entire process was carried out under a nitrogen atmosphere.
[0125] Ruthenium loading of ruthenium-carbon catalyst: The loading was determined by inductively coupled plasma atomic emission spectrometry (ICP-OES). The catalyst sample was completely dissolved by microwave digestion (mixed acid system of concentrated nitric acid and hydrofluoric acid). The concentration of Ru in the solution was detected by ICP-OES. The actual ruthenium loading was calculated by combining the sample mass.
[0126] Microstructure and particle size of ruthenium-carbon catalyst: Characterization and analysis were performed using a Tecnai G2F20 field emission transmission electron microscope (TEM) from FEI Corporation, USA.
[0127] Phase analysis of the ruthenium-carbon catalyst: The crystal structure of the catalyst was characterized using a Rigaku TTR-III polycrystalline X-ray diffractometer (XRD). The test conditions were as follows: scan range 10°–80° (2θ), scan rate 10°·min. -1 .
[0128] Glucose conversion rate: The glucose conversion rate was determined by the Felling reagent chemical titration method. The calculation formula is N=[(V0-V)×0.002×n]÷10; where: N is the glucose content, g / mL; V0 is the Felling reagent calibration value, mL; V is the titration value of the test solution, mL; 0.002 is the concentration of the titrant (glucose), g / mL; 10 is the volume of the test solution, mL; and n is the dilution factor of the test solution.
[0129] Sorbitol selectivity: Sorbitol selectivity (%) = Amount of sorbitol produced ÷ (Amount of initial glucose - Amount of remaining glucose) × 100%. Glucose conversion rate after 8 cycles: After each reaction, the catalyst was recovered by centrifugation, washed 3-5 times with deionized water to remove adsorbed products and impurities, and vacuum dried before being reused for glucose hydrogenation under the same conditions as the first reaction. After 8 cycles, the glucose conversion rate was determined by HPLC. HPLC test conditions: SHIMADZU RID 20A high-performance liquid chromatograph; mobile phase: 0.05 mol / L H2SO4; flow rate: 0.65 mL / min; glycerol as internal standard; glucose and sorbitol content were quantitatively determined by peak area ratio method. The conversion rate retention rate was calculated by comparing with the initial reaction conversion rate: Glucose conversion rate retention rate after 8 cycles = (Initial glucose conversion rate - Glucose conversion rate after 8 cycles) ÷ Initial glucose conversion rate × 100%.
[0130] Table 1
[0131]
[0132] Table 2
[0133]
[0134] Comparative Example 1, lacking activated carbon modification, did not show improvement in the BET specific surface area and pore size distribution of the activated carbon support. The ruthenium-carbon catalyst of Example 1 exhibits excellent mesoporous and hierarchical pore structures, with significant advantages in various pore structure parameters compared to Comparative Example 1. Pore size distribution testing results show that the mesopore sizes of both samples are concentrated in the 3-5 nm range. Example 1 shows a higher peak pore volume at 4 nm, indicating a rich and uniform mesoporous structure, while retaining a certain pore volume in the 10-100 nm macropore range, forming a hierarchical pore structure suitable for the catalytic reaction. In contrast, the peak pore volume of Comparative Example 1 at 4 nm is only 52% of that of Example 1, indicating significantly insufficient mesopore abundance, and the pore volume in the macropore range above 10 nm is almost zero, lacking a hierarchical pore structure.
[0135] The specific surface area and pore size distribution of the modified activated carbon support in Example 1 and the unmodified activated carbon support in Comparative Example 1 are shown in the figure below. Figure 1 As shown, the adsorption-desorption isotherm test indicates that Example 1 has a higher adsorption capacity, corresponding to a larger specific surface area and pore volume, which can provide more active sites for the catalytic reaction. Meanwhile, the hierarchical porous structure of Example 1 can effectively accelerate the diffusion and mass transfer rate between reactants and products, significantly improving catalytic performance. Comparative Example 1, with its low mesopore content, lack of macroporous channels, and poor pore connectivity, cannot achieve efficient mass transfer in the reaction system, thus limiting its overall catalytic performance.
[0136] The modified activated carbon of this invention exhibits a significantly increased BET specific surface area. This larger surface area provides more active sites, enhancing the adsorption and anchoring of ruthenium precursors and effectively preventing ruthenium particle migration and aggregation. Furthermore, it provides a sufficient reaction interface for the glucose hydrogenation reaction, reducing mass transfer and diffusion resistance between reactants and products, and improving catalytic activity. The ample pore volume structure effectively prevents ruthenium particles from accumulating and agglomerating within the pores, while also providing mass transfer and diffusion channels for reactants (glucose) and products (sorbitol). The modified activated carbon, combining a suitable specific surface area with a well-developed pore structure, enhances the binding stability between the ruthenium active component and the support.
[0137] Surface functional groups serve as anchoring points for the active ruthenium precursor. The infrared spectrum of the surface functional groups on the modified activated carbon support in Example 1 is shown below. Figure 2 As shown, it has a diameter of 1100~1180cm. -1 The symmetric S=O stretching vibration peak of the sulfonic acid group at 1300~1370 cm⁻¹ -1 The peak of the asymmetric S=O stretching vibration of the sulfonic acid group at 1680~1720 cm⁻¹ -1 The carbonyl characteristic peak at 3600-3650 cm⁻¹, and the characteristic peak of carbonyl group at 3600-3650 cm⁻¹. -1The presence of hydroxyl absorption peaks indicates that the activated carbon has been modified. The abundant oxygen-containing functional groups provide nucleation sites for the subsequently supported active metal ruthenium, contributing to improved metal dispersibility and catalytic activity. Through interaction with Ru... 2+ Coordination and electrostatic adsorption occur, firmly binding the ruthenium-free intermediate to the activated carbon surface, preventing ruthenium loss during loading. The presence of functional groups can regulate the electronic properties of the activated carbon surface, enhance the interaction between ruthenium and the support (metal-support interaction, SMSI), and inhibit the sintering and growth of ruthenium particles during reduction and reaction. In addition, functional groups such as carboxyl groups can regulate the acid-base environment of the catalyst surface, promote the adsorption and activation of carbonyl groups (C=O) in glucose molecules, and improve the selectivity of hydrogenation reaction.
[0138] TEM images and size distribution diagrams of the ruthenium-carbon catalyst and nano-Ru particles in Example 1 are shown below. Figure 3 As shown, the XRD patterns of the ruthenium-carbon catalysts of Example 1 and Comparative Example 1 are as follows. Figure 4 As shown. Based on the physical confinement and regulation effect of the hierarchical pore structure, the average particle size of the active metal ruthenium (Ru) in the catalyst prepared in Example 1 is 4.2 nm. Transmission electron microscopy characterization results show that the Ru active component can be uniformly dispersed on the surface of the catalyst support, with not only uniform particle size and small overall particle size, but also no obvious particle agglomeration. Combined with X-ray diffraction (XRD) characterization: the characteristic diffraction peak at 44° of the sample XRD pattern is completely matched with the characteristic peak of the (101) crystal plane of the Ru standard card (PDF#06-0663), and the characteristic diffraction peak shows obvious broadening, which confirms that the active Ru particles in the catalyst are small in size, which is highly consistent with the microstructure observation results of transmission electron microscopy. Compared with the ruthenium-carbon catalyst of Comparative Example 1, the ruthenium-carbon catalyst of Example 1 has a higher intensity of the characteristic diffraction peak of the Ru (101) crystal plane, indicating that its active metal Ru has better crystallinity. A well-ordered crystal structure can effectively optimize the microstructure of active sites on the catalyst surface, reduce the adverse effects of structural defects on the catalytic reaction, and provide favorable structural conditions for improving the catalytic activity of the catalyst in glucose hydrogenation.
[0139] The catalytic activity characterization liquid chromatography (HPLC) chromatogram of the ruthenium-carbon catalyst in Example 1 is shown below. Figure 5As shown. To evaluate the hydrogenation catalytic performance of this catalyst, high-performance liquid chromatography (HPLC) was used to qualitatively and quantitatively detect the hydrogenation reaction products of pure glucose, pure sorbitol standard solution, and glucose in Example 1. Based on the chromatographic peak area, the chromatographic retention times of glucose and sorbitol were determined to be 10.70 min and 11.73 min, respectively. No obvious impurity peaks were observed in the product HPLC chromatograms, indicating that the catalyst exhibits virtually no side reactions during the glucose hydrogenation process and demonstrates excellent catalytic selectivity for sorbitol. The conversion rate of glucose as a function of reaction time (the conversion rate and selectivity of the ruthenium-carbon catalyst in Example 1 are shown in Figure 1) further supports this assessment. Figure 6 As shown in the figure, comprehensive analysis further confirms that the Ru-based hydrogenation catalyst prepared in Example 1 possesses excellent catalytic activity for glucose hydrogenation.
[0140] In Comparative Example 2, the absence of a complexing agent led to the easy hydrolysis and aggregation of ruthenium intermediates during deposition, making it difficult to form uniform monodisperse adsorption sites on the support surface and ultimately reducing the dispersibility of the active component. In Comparative Example 3, the lack of sintering prevented the formation of strong metal-support interactions between ruthenium nanoparticles and the activated carbon support; the ruthenium particles adhered to the support surface only through physical adsorption, resulting in weak interfacial bonding strength. Under reaction conditions, migration, detachment, and loss easily occurred, causing rapid activity decay during catalyst recycling.
[0141] Comparative Example 4, due to the use of a conventional ruthenium salt solution, resulted in ruthenium existing in the form of a stable ruthenium chloride complex ion, with residual Cl... - Ruthenium intermediates strongly adsorb onto the catalyst surface, poisoning active sites, inhibiting hydrogenation reactions, and reducing sorbitol selectivity. In Comparative Example 5, due to the lack of supercritical fluid deposition, ruthenium intermediates relied solely on liquid-phase impregnation for diffusion and mass transfer, resulting in high mass transfer resistance. This method led to a large accumulation of ruthenium intermediates on the outer surface of the support, causing particle agglomeration on the support surface, insufficient loading of active components inside the pores, and poor overall dispersion of active components. In Comparative Example 6, the use of a conventional deposition scheme resulted in difficulty in achieving molecular-level uniform dispersion and deep penetration of ruthenium intermediates into the support pores. Furthermore, during the drying and heat treatment stages, ruthenium species were prone to migration and agglomeration, further deteriorating the catalyst structure and performance.
[0142] As can be seen from the above, compared with the comparative example, the present invention uses activated carbon that has been synergistically modified by mixed acid oxidation treatment and gas phase heating activation as a support, and ruthenium metal as an active component. The ruthenium-carbon catalyst is prepared through a stepwise process of "support pretreatment modification, preparation of chlorine-free ruthenium intermediate, complexation impregnation, supercritical deposition, liquid phase reduction, and sintering activation". The prepared catalyst has high dispersion of active components, strong interaction with the support, and simple preparation process. It exhibits high catalytic activity in the glucose hydrogenation reaction, significantly improves glucose conversion rate and sorbitol selectivity, and its performance remains stable after multiple cycles. It can realize the efficient conversion of glucose to sorbitol under mild conditions.
[0143] Furthermore, it can be seen that the overall effect is better when all process parameters are within the preferred range of the present invention.
[0144] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a ruthenium-carbon catalyst, characterized in that, Includes the following steps: Step S1: Oxidize activated carbon with acid to obtain oxidized activated carbon; activate the oxidized activated carbon with an oxygen-nitrogen mixed gas to obtain modified activated carbon; the volume fraction of O2 in the oxygen-nitrogen mixed gas is 5.0~10.0%, and the gas flow rate is 150~250mL / min; the activation temperature is 250~350℃, the time is 1~3h, and the heating rate is 2~5℃ / min. Step S2: The ruthenium salt is mixed with the surfactant and the first solvent to obtain a ruthenium salt solution. CO gas is introduced to carry out a reduction reaction, followed by the addition of ammonia water to carry out a hydrolysis reaction to obtain a ruthenium(II) hydroxycarbonyl polymer. Step S3: The ruthenium(II) hydroxycarbonyl polymer is mixed with a complexing agent and a second solvent to obtain an active raw material solution. The modified activated carbon is added for impregnation to obtain an impregnation solution. The impregnation solution is transferred into a reaction vessel and supercritical fluid is introduced for supercritical fluid deposition to obtain a ruthenium-loaded pretreated carrier. Step S4: Disperse the ruthenium-supported pretreated support in water, add a reducing agent, and carry out a reduction reaction to obtain a catalyst precursor; Step S5: The catalyst precursor is sintered under an inert atmosphere to obtain the ruthenium-carbon catalyst; the ruthenium-carbon catalyst contains nano-ruthenium particles; the inert atmosphere is one or more of nitrogen, argon and helium.
2. The method for preparing the ruthenium-carbon catalyst according to claim 1, characterized in that, The ruthenium nanoparticles have a particle size Dv50 of 2~8 nm and a particle size distribution range A = Dv90 - Dv10, where A ≤ 5 nm; and / or Based on the total weight of the ruthenium-carbon catalyst (100.0%), the ruthenium loading of the ruthenium-carbon catalyst is 1.0~5.0 wt%; and / or The modified activated carbon has a BET specific surface area of 750~1200m² / g and a pore volume of 0.8~1.5cm³ / g; and / or The modified activated carbon has oxygen-containing functional groups on its surface, including one or more of carboxyl, hydroxyl, and sulfonic acid groups, and the content of the oxygen-containing functional groups is 0.5~2.0 mmol / g.
3. The method for preparing the ruthenium-carbon catalyst according to claim 1 or 2, characterized in that, In step S1 The activated carbon has a particle size of 20-100 mesh, a BET specific surface area of 700-1100 m² / g, and a pore volume of 0.6-1.2 cm³ / g; and / or The acid solution comprises concentrated nitric acid and concentrated sulfuric acid in a volume ratio of (2~3):1; and / or The oxidation is carried out at a temperature of 80~120℃ for a time of 3~8 hours; and / or Before the heating and activation, the process includes the following steps: washing the oxidized activated carbon with water until the pH of the washing solution is 5.5~6.5, and then drying it at 105~110℃ for 4~6 hours.
4. The method for preparing the ruthenium-carbon catalyst according to claim 1 or 2, characterized in that, In step S2 The ruthenium salt includes one or more of hydrated ruthenium trichloride, chlororuthenic acid, sodium chlororuthenate, and potassium chlororuthenate; and / or The surfactant includes one or more of stearic acid, Tween, sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, hexadecyltrimethylammonium bromide, and Span; and / or The first solvent includes one or more of water, hydrochloric acid, ethanol, and methanol; and / or The CO gas flow rate is 30~120 mL / min; and / or In the ruthenium salt solution, the molar concentration of the ruthenium salt is 0.05~0.2 mol / L; and / or In the ruthenium salt solution, the surfactant has a weight percentage of 0.01~1.0%; and / or The pH value of the ruthenium salt solution after the addition of the ammonia water is 7.5~10.0; and / or The mass concentration of the ammonia solution is 5.0~15.0%; and / or The reduction reaction is carried out at a temperature of 55-85°C for a time of 4-10 hours; and / or The hydrolysis reaction is carried out at a pH of 7.5-10.0, a temperature of 30-60℃, a time of 3-6 hours, and a stirring rate of 300-800 rpm.
5. The method for preparing the ruthenium-carbon catalyst according to claim 1 or 2, characterized in that, In step S3 The complexing agent includes one or more of ethylenediamine, citric acid, oxalic acid, ammonium chloride, and aminotriacetic acid; and / or The second solvent includes one or more of water, ethanol, and methanol; and / or The supercritical fluid includes one or more of supercritical CO2, supercritical N2O, and supercritical NH3; and / or In the active raw material solution, the molar concentration of ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer is 0.01~0.5 mol / L; and / or The molar ratio of the complexing agent to the ruthenium atoms in the ruthenium(II) hydroxycarbonyl polymer is (0.01~3):1; and / or The impregnation temperature is 30~60℃, the time is 6~12h, and the stirring rate is 150~300rpm; and / or The conditions for supercritical fluid deposition include: heating the reactor to 50-150°C, maintaining the pressure at 5.0-15.0 MPa for 1-3 hours, and stirring at 200-400 rpm; after the reaction is complete, cooling the reactor to room temperature at a rate of 1-2°C / min, and releasing the gas inside the reactor at a pressure relief rate of less than 0.5 MPa / min; and / or The supercritical fluid deposition process further includes the following steps: washing the ruthenium-loaded pretreated carrier alternately with water and anhydrous ethanol 3 to 5 times, and then vacuum drying at 80 to 100°C for 6 to 8 hours with a vacuum degree ≤ -0.09 MPa.
6. The method for preparing the ruthenium-carbon catalyst according to claim 1 or 2, characterized in that, In step S4 The reducing agent includes one or more of potassium borohydride, sodium borohydride, hydrazine hydrate, sodium citrate, and ascorbic acid; and / or The molar ratio of the reducing agent to the ruthenium atoms in the ruthenium-loaded pretreated support is (2~5):1; and / or The reducing agent is added in the form of a reducing agent solution; wherein the solvent of the reducing agent solution includes one or more of ethylene glycol, ethanol, and water; and / or, the molar concentration of the reducing agent solution is 0.1~0.5 mol / L, the dropping rate is 1~5 mL / min, and stirring continues for 30~60 min after the dropping is completed; and / or The reduction reaction is carried out under ice-water bath conditions, with a temperature of 0-5°C and a duration of 1-3 hours; and / or The reduction reaction further includes the following steps: solid-liquid separation of the feed liquid, washing the solid product with water until the washing liquid is free of chloride ions, and then vacuum drying at 80~100℃ for 4~6h, with a vacuum degree ≤-0.09MPa.
7. The method for preparing the ruthenium-carbon catalyst according to claim 1 or 2, characterized in that, In step S5, the sintering temperature is 300~400℃, the time is 2~4h, the heating rate is 2~5℃ / min, and the flow rate of the inert atmosphere is 100~200mL / min.
8. A ruthenium-carbon catalyst, characterized in that, The ruthenium-carbon catalyst is obtained according to any one of claims 1 to 7.
9. A method for preparing sorbitol by hydrogenation of glucose, characterized in that, Glucose, water, and the ruthenium-carbon catalyst of claim 8 are mixed and subjected to catalytic hydrogenation to obtain sorbitol.
10. The method for preparing sorbitol by hydrogenation of glucose according to claim 9, characterized in that, The weight ratio of the ruthenium-carbon catalyst to the glucose is (0.5~2.0):100; and / or The catalytic hydrogenation temperature is 100~140℃, the hydrogen pressure is 2.0~5.0MPa, and the time is 1~3h.
Citation Information
Patent Citations
Preparation method of nano Ru / C supported catalyst
CN105498761A
Method for preparing sugar alcohol through catalytic hydrogenation
CN113233961A